2021
DOI: 10.3389/fimmu.2021.594270
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomic Profiling of the Correlation Between Prognosis Differences and PD-1 Expression in Sepsis: A Preliminary Study

Abstract: Objectives: The mortality rate of sepsis remains very high. Metabolomic techniques are playing increasingly important roles in diagnosis and treatment in critical care medicine. The purpose of our research was to use untargeted metabolomics to identify and analyze the common differential metabolites among patients with sepsis with differences in their 7-day prognosis and blood PD-1 expression and analyze their correlations with environmental factors.Methods: Plasma samples from 18 patients with sepsis were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Numerous studies have proven that coinhibitory markers such as PD-1 are highly expressed on T cells, and are associated with T-cell apoptosis during sepsis. [23][24][25] That anti-PD-1/PD-L1 has been shown to improve survival in cecal ligation and puncture (CLP) model mice and has entered clinical trials in patients with sepsis. [26][27][28] Our study first reported that it is memory CD4 + T cells and memory CD8 + T cells, rather than naive CD4 + T cells and naive CD8 + T cells, that played critical role in PD-1 mediating signaling in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have proven that coinhibitory markers such as PD-1 are highly expressed on T cells, and are associated with T-cell apoptosis during sepsis. [23][24][25] That anti-PD-1/PD-L1 has been shown to improve survival in cecal ligation and puncture (CLP) model mice and has entered clinical trials in patients with sepsis. [26][27][28] Our study first reported that it is memory CD4 + T cells and memory CD8 + T cells, rather than naive CD4 + T cells and naive CD8 + T cells, that played critical role in PD-1 mediating signaling in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The immunosuppressive molecules, such as PD-1, with increased expression on various types of immune cells, are one of the important mechanisms underlying immunosuppression in sepsis ( 11 , 12 ). It has been reported that the higher the percentage of PD-1 + monocytes, the higher the possibility of nosocomial infection in patients with sepsis ( 7 ). However, PD-1 expression on CD4 + or CD8 + T cells had no effect on nosocomial infection as shown in the study, and this corroborates with finding in a previous report by Wilson et al ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Programmed death 1 (PD-1), an immunoreceptor tyrosine-based inhibitory motif–containing receptor or an inhibitory member of the CD28 family, expressed on activated T cells, B cells, and monocytes and likely regulates these cell types ( 6 ), may be related to nosocomial infection in patients with sepsis. Among septic shock patients, elevated PD-1 combined with PD–ligand 1 of CD4 + T cell resulted in increased nosocomial infections and mortality ( 7 ). This may be attributed to PD-1 interacted with PD-1 combined with PD–ligand 1 of antigen-presenting cells (APCs) that inhibited CD4 + or CD8 + T cells and reduced interleukin 2 (IL-2) production ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectrometry and “omics” strategies allow for untargeted profiling of thousands of proteins and metabolites from human biological samples obtained from septic patients. Differential expression of, or modifications to, these proteins and metabolites provides a more reliable source of diagnostic biomarkers for sepsis ( 135 , 137 ).…”
Section: Mass Spectrometry Characterization Applied To Infectious Dis...mentioning
confidence: 99%